2020
DOI: 10.31235/osf.io/8tvxk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The lived experience of COVID-19: housing and household resilience

Abstract: This study investigated housing outcomes during the first three months of the COVID-19 pandemic, and evaluated the complex interrelated impacts it is having on Australian households with a range of vulnerabilities. COVID-19 has exacerbated vulnerabilities such as poor housing quality and location; housing affordability; energy poverty and a range of social, mental and physical health conditions.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Data were collected between June and August 2020, when strict Covid-19 restrictions were still in place. The timing of this data collection enabled a particular focus on how homes were used and experienced during the pandemic, when existing work, care, and domestic labour practices were severely disrupted, our relationships to home and the meanings of home were altered (Byrne, 2020;Devine-Wright et al, 2020), and issues of housing quality were exacerbated (Brown et al, 2020;Byrne & Sassi, 2022;Horne et al, 2020;Soaita, 2021). In this paper, our analysis complements and builds on the studies discussed in the preceding paragraph through its focus on how a range of residents of working age in London experience the spatiality and affordances of their dwellings, and on how these experiences were challenged in the Covid-19 pandemic (in particular in relation to household dynamics and home working practices).…”
Section: Introductionmentioning
confidence: 99%
“…Data were collected between June and August 2020, when strict Covid-19 restrictions were still in place. The timing of this data collection enabled a particular focus on how homes were used and experienced during the pandemic, when existing work, care, and domestic labour practices were severely disrupted, our relationships to home and the meanings of home were altered (Byrne, 2020;Devine-Wright et al, 2020), and issues of housing quality were exacerbated (Brown et al, 2020;Byrne & Sassi, 2022;Horne et al, 2020;Soaita, 2021). In this paper, our analysis complements and builds on the studies discussed in the preceding paragraph through its focus on how a range of residents of working age in London experience the spatiality and affordances of their dwellings, and on how these experiences were challenged in the Covid-19 pandemic (in particular in relation to household dynamics and home working practices).…”
Section: Introductionmentioning
confidence: 99%
“…Since COVID-19 weakened the public ability to afford rent, mortgages, and home repairs [28], real estate economy data (including property management fees, housing prices, and housing rent) were also introduced to complement independent variables. The unit of these three economic indicators was unified as "RMB/square meter.…”
Section: Real Estate Economymentioning
confidence: 99%
“…The overall pandemic experiences of families [ 6 ] and specific experiences of adults who test positive for COVID-19 is being investigated, but little is known about the impact of a positive test on the child, parents and families [ 7 , 8 ]. In one qualitative study of 11 COVID-positive adult patients in New South Wales [ 7 ], five themes were identified to describe participants’ experiences in an isolation facility: knowing about COVID-19; planning for, and responding to, COVID-19; being infected; life in isolation and the room; and post-discharge life.…”
Section: Introductionmentioning
confidence: 99%